The structure of financial systems and macroeconomic instability - Daniel Gros; Karel Lannoo (EIB Papers, 1999)
With the successful launch of the euro, the previously national interbank bank markets have been integrated at once in a unified euro interbank market, outstanding public debt has been redenominated in euro, trading conventions harmonised, and all EMU stock markets have started quoting in euro. This does not, however, bring Euroland at once to a US-style capital market, since it remains profoundly different from the US in at least two aspects: Regional differences: The terms and conditions under which enterprises finance investment and the role of intermediaries still vary considerably from country to country in the EU. This is due to deeply-rooted structural differences in legal systems, development of markets and institutions, and the role of the state. The importance of banks: Bank credit plays a much more important role than market-based forms of financing of investments by enterprises in the EU. Disintermediation, and institutionalisation of savings in pension and investment funds is much less developed than in the US. These differences have acquired a special importance because financial markets are subject to important shocks at present. In this paper we focus on how the structure of the financial system influences the way in which financial market volatility impinges on the real economy. In a nutshell, a bank-based system usually absorbs high frequency shocks better than a market-based system; however, a bank-based system has other problems, especially in the area of supervision, where the framework for EMU has not yet been well defined. These two points are vividly reflected in the different responses of the US and European monetary authorities to the market developments induced by the Russian debt moratorium of August 1998. Just trying to imagine how the European supervisory and monetary authorities would have reacted to something like the LTCM collapse in the EU is a good way to see the importance of these two points.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Finanzmarkt; Wirtschaftliche Instabilität; EU-Staaten